Narrowband and Pure Violet Organic Emitter with a Full Width at Half Maximum of 14 nm and y Color Coordinate of Below 0.02. Issue 14 (12th March 2020) - Lee, Ha Lim; Chung, Won Jae; Lee, Jun Yeob
Abstract: Violet organic light‐emitting diodes (OLEDs) with a very narrow emission spectrum with a full width at half maximum of 14 nm and y color coordinate of 0.02 are developed using a indolo[3, 2, 1‐ jk ]carbazole‐derived pure violet emitter. The violet emitter, 2, 5, 13, 16‐tetra‐ tert ‐butylindolo[3, 2, 1‐ jk ]‐indolo[1′, 2′, 3′:1, 7]indolo[2, 3‐ b ]carbazole (tDIDCz), is designed to have a very rigid molecular structure driven by the multiresonance‐type core structure through the alternating carbon and nitrogen atoms. The violet emitter is decorated with t ‐butyl groups to prevent intermolecular aggregation and packing, which allow pure violet emission without excimer emission. The violet OLEDs derived from the tDIDCz emitter show a violet color coordinate of (0.164, 0.018) with a narrow emission spectrum and a full width at half maximum of 14 nm (105 meV). The external quantum efficiency of the pure violet OLEDs is 3.3%. This is the first work reporting pure violet emission without any ultraviolet emission below 380 nm and blue emission above 450 nm by showing a very narrow emission spectrum. Abstract : A 2, 5, 13, 16‐tetra‐ tert ‐butylindolo[3, 2, 1‐ jk ]indolo[1′, 2′, 3′:1, 7]indolo[2, 3‐ b ]carbazole (tDIDCz) is developed as a violet emitter with a narrow emission spectrum with a full width at half maximum of 14 nm, pure violet color coordinates of (0.164, 0.018), and an external quantum efficiency of 3.3%.